Development of an Islamic Education Management Philosophy e-Module through the Canva Application - Nurmayuli Nurmayuli (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study aims to create e-modules for Islamic Education Management Philosophy lectures using the Canva Design tool, which will include material descriptions, videos, and activities for each material sub-chapter. The ADDIE model research and development process was applied. The responders were 67 students from Ar-Raniry State Islamic University's Islamic Education Management Study Program for the 2020/2021 academic year. Analysis, design, development, implementation, and evaluation are the five stages of research. The product validation results from the two validators obtained an average score of 77.50% in the feasible category and a high score with a percentage ranging from 86.19% to 92.53% at the implementation stage, indicating that the Islamic Education Management Philosophy e-module is very feasible to use and very helpful to students in Islamic education management philosophy lectures. The user's feedback is that this student e-module is simple to use and beneficial in Islamic Education Management Philosophy classes. Based on student comments, it is possible to infer that the Islamic education management philosophy e-module is an excellent e-module to be utilized as a learning resource that is highly suited in the current and future period of autonomous learning.